Growth and condition features of progenies of plus and best Quercus robur L. trees of Trostyanets origin - Los, S. A.; Samoday, V. P.; Godovany, A. N.; Grigorieva, V. G.; Plotnikova, O. M.; Gubin, E. A. (Forestry and Forest Melioration, 2020)
Introduction Establishment and research of progeny tests are a part of forest tree improvement programmes in many countries around the world (Bogdan et al. 2004, Review 2011, North Carolina 2018, Hayda 2019, Hossain et al. 2020, Oweviev 2020, Plus tree 2020). The main aim of such testing is to select elite trees to establish clonal seed orchards of the second and higher levels. The testing assesses, first of all, the intensity of growth, but a need for an integrated approach is emphasized (Methods 2019, Overview 2020). The oak progeny tests in different regions in Ukraine by growth rate, health and stem quality have shown that about 20 % of the trees are promising (Hayda et al. 2010, Los 2016, Los et al. 2009, 2012, 2017). However, the analysis of test results of the plus trees progenies of different geographical origin provides an opportunity to identify certain patterns (Hayda et al. 2010, 2011). The aim of the study was to compare the growth rate, quality and condition of 62-year-old offspring of plus and the best English oak trees of Trostyanets origin in Kharkiv and Sumy Regions. Materials and Methods The study was carried out in the oldest in Ukraine progeny test of English oak in Kharkiv and Sumy Regions, where in 1958 the seeds of 20 the best English oak trees selected in the forests of Trostyanets State Forest Enterprise were sown. At the end of the growing season in 2019, when the biological age of plants was 62 years, an observation of both plots was carried out. The diameter, height, stem straightness, condition of the tree were determined as well as the presence of defects and damage. The obtained data were processed by the methods of variation statistics and the significance of differences between the variants and the control was determined. The final conclusion on the selection value of plus and the best trees was made following the comprehensive assessment. Results In the test plot in Kharkiv Forest Research Station the average diameter of the progenies at the age of 62 ranged from 15.9 (Tr-5) to 37.5 cm (Tr-2). The last variant significantly exceeded the control by 51.7%. Variants Tr-3 and Tr-5 significantly fell behind the control by an average of 25.1%. The average height of the progenies was in the range from 21.2 to 25.8 m. The progenies of trees Tr-2, Tr-15, Tr-16, and Tr-18 significantly exceeded the control by an average of 6.9%. The rest of the progenies grew at the level of the control. The average diameters of the progenies at Trostyanets State Forest Enterprise ranged from 22.0 to 44.0 cm. Only the Tr-1 variant significantly exceeded the control by 9.1%, and Tr-6 was significantly inferior by 9.1%. The average height of the progenies ranged from 25.0 m (Tr-18) to 30.5 m (Tr-2). The progenies Tr-1 and Tr-15 significantly exceeded the control in height by 4.1%. The variants Tr-4, Tr-11, Tr-16, and Tr-18 fell significantly behind the control by 3.3%. The rest of the progenies grew at the level of the control. The advantages of the most intensively growing variant (Tr-2) proved to be insignificant due to a small number of survived trees. In almost all cases, both the average diameter and height of the variants were larger in the plot in Trostyanets State Forest Enterprise. The difference in average heights ranged from 0.6 to 6.0 m. The average diameter was greater by 2.7–15.6 cm. Thus, the volume of the average tree was higher by 0.3 m3 to 1.0 m3 and ranged from 0.45 m3 to 2.12 m3 (in Trostyanets State Forest Enterprise it was from 0.25 m3 to 1.38 m3). This can be explained by higher precipitation level and, consequently, better humidification conditions. The average annual precipitation in Kharkiv is 528 mm, and it is 330 mm during the growing season, while in Trostyanets these figures are 631 mm and 417mm, respectively. The average annual temperature of the regions is the same: +7.5°C, and during the growing season differs by 0.7°C (14.9°C and 14.2°C). The calculations show that a decrease in annual precipitation by 10 mm resulted in a decrease in the average height of oak plantations by 2.2%, the average diameter by 3.5 % and the volume of the average tree by 3.2 %. Reducing the amount of precipitation during the growing season by 10 mm will reduce the average height of the oak by 2.6 %, the average diameter by 4.1 % and the volume of the average tree by 15.7 %. It should be noted that such calculations are only preliminary and cannot be extrapolated to other regions or other species. The variants condition index ranged from 2.0 (Tr-17) to 3.2 (Tr-5) in Sumy Region and from 2.0 (Tr-2) to 3.3 (Tr-3, Tr-15) in Kharkiv Region. There were no variants with unsatisfactory condition. Variants Tr-2, Tr-6, Tr-12, Tr-13, Tr-16, and Tr-18 turned out to be the most drought-resistant in drier conditions of Kharkiv Region. According to the results of the complex assessment, the progenies in Kharkiv Forest Research Station scored from 8 (Tr-5) to 16 (Tr-2) points and in Trostyanets State Forest Enterprise from 6 (Tr-18) to 17 (Tr-2) points. The promising variants were Tr-2, Tr-6, Tr-13, and Tr-18 in the progeny tests in Kharkiv Forest Research Station and Tr-2, Tr-3, Tr-6, Tr -11, and Tr-13 in Trostyanets State Forest Enterprise. Three variants were the leaders in both test plots. Conclusions At the progeny test in Kharkiv Forest Research Station, the best variant (Tr-2) among the progenies of plus and best trees of Trostyanets origin significantly exceeded the control by 51.7% in diameter and by 12.4% in height. According to the comprehensive assessment, four promising variants were identified in progeny tests in Kharkiv Forest Research Station and five variants were recognized in Trostyanets State Forest Enterprise. The mother trees of these progenies can be recommended for vegetative propagation and establishment of clonal seed orchards of the second level in relevant regions. Higher precipitation level and, accordingly, better humidification conditions in Sumy region had a positive effect on the growth of the plus trees progeny in Trostyanets State Forest Enterprise. According to the preliminary calculations, a decrease in annual precipitation by 10 mm reduces the height of oak by 2.2%, its diameter by 3.5% and the volume of the average tree by 3.2% on average. A decrease in the amount of precipitation during the growing season by 10 mm results in a decrease in height by 2.6%, in diameter by 4.1%, and in volume of the average tree by 15.7% on average. 4 Figs., 2 Tables, 16 Refs. Key words: English oak, progeny test, breeding category, complex assessment.